(untitled) (Mongolian Journal of Agricultural Sciences, 2015)
Herbicides, if used properly, are safe and effective in controlling weeds in soybean. The choice of herbicide, however, depends on the predominant weed species and the availability of the herbicide. Chemical control is currently the most widely used control for soybean crops, due to its ease of control and to the small areas planted in Mongolia. In the soybean field the 15species of weeds belonging to 9 families, 12 genus including 62.5 % annual, 37.5%perennial weeds are distributed.The major grassy weeds; Common millet-(Panicummiliaceum L), Couch grass-(Agropyronrepens L), Bristlegrass-(Seteriaviridis L) sp and broadleaved weeds Redroot Pigweed-(Amaranthtusretro flexus),lambs guarters-(Chenopodium album), AristateGoosfoot-(Chenopodiumaristatum L), Black bindweed-(Polygonum convolvulus), Mallow weed-(Malvamochileviensis Down), Field bindweed-(Convolvulus arvensis), Bristhly thistle-(Cirsiumsetosum ), Dwarf bifurcate cinquefoil -(Potentillabifurca), Perennial Sowthisle-(Sonchusarvensis L) weeds have been distributed in the soybean field.In soybean field the Forward herbicide were applied in doses of 1.0-1.2l/ha have reduced the number of weeds by 90.1-91.6%, weight by 59.5-66.1% and super herbicide Gallantsuper applied in doses of 0.45-0.65l/ha have reduced the number of weeds by 91.0-95.0%, weight by 39.5-59.8% while Cobra herbicide applied in doses of 0.45-0.55l/ha used in broadleaved weed distributed field, have reduced the number of weeds by 90.2-94.6% and weight by 42.7-50.7%. The herbicide application increased of yield hectare by 3.6-9.0 center. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 76-79